Computer-associated health complaints and sources of ergonomic instructions in computer-related issues among Finnish adolescents: A cross-sectional study - Ketola Ritva L; Saarni Lea A; Hakala Paula T; Rahkola Erja T; Salminen Jouko J; Rimpelä Arja H (BMC, 2010)
Abstract Background The use of computers has increased among adolescents, as have musculoskeletal symptoms. There is evidence that these symptoms can be reduced through an ergonomics approach and through education. The purpose of this study was to examine where adolescents had received ergonomic instructions related to computer use, and whether receiving these instructions was associated with a reduced prevalence of computer-associated health complaints. Methods Mailed survey with nationally representative sample of 12 to 18-year-old Finns in 2001 (n = 7292, response rate 70%). In total, 6961 youths reported using a computer. We tested the associations of computer use time and received ergonomic instructions (predictor variables) with computer-associated health complaints (outcome variables) using logistic regression analysis. Results To prevent computer-associated complaints, 61.2% reported having been instructed to arrange their desk/chair/screen in the right position, 71.5% to take rest breaks. The older age group (16-18 years) reported receiving instructions or being self-instructed more often than the 12- to 14-year-olds (p < 0.001). Among both age groups the sources of instructions included school (33.1%), family (28.6%), self (self-instructed) (12.5%), ICT-related (8.6%), friends (1.5%) and health professionals (0.8%). Receiving instructions was not related to lower prevalence of computer-associated health complaints. Conclusions This report shows that ergonomic instructions on how to prevent computer-related musculoskeletal problems fail to reach a substantial number of children. Furthermore, the reported sources of instructions vary greatly in terms of reliability.